REGIONAL CULTURE IN THE CONTEXT OF IDEAS OF RUSSIAN THINKERS - I. V. Gorina (Дискурс, 2016)
The article focuses on conceptual notions of culture typology of Danilevsky N. I, "local history" of V. O. Klyuchevskii, ontology of "cult" of Rozanov, V. V., "travel to the culture” of Graves M., activity approach of Kagan M. S. relevant to the contemporary study of regional culture.